Problem formulation as a purposive activity - Volkema, Roger J. (Strategic Management Journal, 1986)
Abstract This paper presents a framework for understanding the multiple purposes that problem statements can serve during the formulation phase of strategic planning. Both functional and dysfunctional purposes exist. Variables that can help to identify dysfunctional purposes are discussed.